Milk urea nitrogen: a nutritional management tool - Dunham, James R. (Kansas Agricultural Experiment Station, 2011)
Milk urea nitrogen (MUN) analyses can be used to evaluate the nutritional status of dairy herds and for fine tuning the feeding program. MUN values >18 mg/100 ml indicate that dietary protein is being wasted and feed costs could be reduced with ration adjustments. Higher than desired MUN values also indicate the need for additional undegradable intake protein (UIP; bypass protein) in the ration. High MUN values can also indicate the need for more nonstructural carbohydrates (NSC) in the diet. MUN readings <14 mg/100 ml indicate dietary crude protein deficiencies or too much UIP in the ration. Reduced milk production or low milk protein tests can occur when feeding rations that produce low MUN tests. Poor reproductive performance may be the result of feeding rations that produce high MUN measurements. Conception rates may be reduced as much as 20 percentage points when MUN is >18 mg/100 ml.
Keywords: Milk urea nitrogen; nutrition management; Conception rates; Protein